Digital technology in dental education during COVID-19 pandemic : worldwide experience of professors and students = Tecnología digital en la educación odontológica durante la pandemia por COVID-19 : experiencia mundial de profesoresy estudiantes - Dantas Costa, Eliana
The objective of this study was to assess the use and experience with digital communication tools among dentistry professors and students to adapt to distance learning during the Covid-19 pandemic. Nine hundread and ninety five participants (479 dentistry professors and 516 students) from countries in North America, Latin America, Brazil, Europe, Asia, Oceania, and the Middle East answered a questionnaire about motivation/stress/anxiety; practice with digital technologies; synchronous/asynchronous communication technologies (difficulties/benefits), and which ones would they prefer using when returning to college. Data were analyzed by the Chi-square test and Fisher's exact (α=0.05). Motivation was more affected among the female professors, male students, and Brazilians (p<0.05). Concern about the academic future, was higher among female students, up to 30 years old, from Latin America and Brazil, and lower for European professors (p<0.05). Anxiety and stress were higher for undergraduate students up to 20 years old from Latin America and Brazil (p<0.05). European professors used more synchronous videoconferencing services for lectures/questions, while Brazilians used more text messaging applications for answering questions (p<0.05). Latin American professors used more surveys for evaluation (p<0.05). Brazilian professors indicated that they would use "online meetings" and "survey administration services" when returning to face-to-face activities and European professors/students would use "email" (p<0.05). Professors from Asia/Oceania/Middle East and professors/students from Brazil indicated "remote activities were important for students not to be inactive" (p<0.05). Efforts were made to adapt Dentistry's teaching to distance learning during the COVID-19 pandemic. However, the technologies used for this, feelings, and experiences differed between professors and students.